Uroflowmetry Findings in Patients with Bladder Outlet Obstruction Symptoms in Standing and Crouching Positions - Amjadi, Mohsen; Madaen, Seyed Kazem; Madaen, Seyed Kazem; Pour-Moazen, Hamid; Pour-Moazen, Hamid (Urology Journal, 2009)
Introduction: Bladder emptying in crouching position is a conventional way in many eastern countries. Our aim was to evaluate uroflowmetry parameters as an index of obstruction severity in standing and crouching positions and comparison of them in patients with bladder outlet obstruction symptoms. Materials and Methods: Uroflowmetry in standing and crouching positions was done in 83 patients with bladder outlet obstruction symptoms due to benign prostatic hyperplasia (BPH). The patients were 50 years old or older and their maximum flow rate in standing position was less than 15 mL/s. The maximum flow rate, average flow rate, maximum flow time, and postvoid residual urine volume were measured and recorded. The results in standing and crouching positions were compared. Results: The mean maximum flow rate and mean average flow rate in crouching position increased 86% and 51%, respectively (P < .001; P = .012), while mean maximum flow time and postvoid residual volume decreased 40% and 46%, respectively (P < .001; P < .001). These changes were also significant in patients with maximum flow rates of less than 10 mL/s and 10 mL/s to 15 mL/s in standing position, except for the maximum flow time in the latter group. Conclusion: A more complete emptying of bladder in crouching position in patients with BPH can be attributed to the increased bladder pressure due to a good transmission of intra-abdominal pressure and a complete and coordinated relaxation of pelvic floor muscles. This position can help improve patients’ symptoms.